2020
DOI: 10.1186/s13287-020-02054-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the impact of cryopreservation on human bone marrow-derived mesenchymal stem cells: up to 24 h post-thaw and beyond

Abstract: Background The effects of cryopreservation on human bone marrow-derived mesenchymal stem cells (hBM-MSCs) are still ill-defined. In this study, a quantitative approach was adopted to measure several post-thaw cell attributes in order to provide an accurate reflection of the freezing and thawing impact. Methods Fresh and cryopreserved passage-matched cells from three different donors were discretely analysed and compared for their viability, apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
2
24
2
Order By: Relevance
“…In contrast, a study comparing BM-MSCs in fresh, freshly thawed, and 24-hour-culture-rescue post-thaw conditions indicated that compared to the other two groups, the freshly thawed group showed decreased CD44 and CD105 expression, decreased proliferation and clonogenic capacity associated with increased apoptosis 7 . Supporting these results, Bahsoun et al recently reported that cryopreservation altered the cellular and functional potency of BM-MSCs and that a 24 h rescue did not fully recover the properties of the cells 14 . The diverse observations might be due to the different tissue sources and culture conditions used in these studies.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, a study comparing BM-MSCs in fresh, freshly thawed, and 24-hour-culture-rescue post-thaw conditions indicated that compared to the other two groups, the freshly thawed group showed decreased CD44 and CD105 expression, decreased proliferation and clonogenic capacity associated with increased apoptosis 7 . Supporting these results, Bahsoun et al recently reported that cryopreservation altered the cellular and functional potency of BM-MSCs and that a 24 h rescue did not fully recover the properties of the cells 14 . The diverse observations might be due to the different tissue sources and culture conditions used in these studies.…”
Section: Discussionmentioning
confidence: 75%
“…Previously, functional differences between pre-freeze (fresh) and post-freeze MSCs were also reported by others [ 43 , 44 ]. Cryopreservation has been shown to affect viability, apoptosis and metabolic activity for up to 24 h post plating and this can be tissue source or donor-related [ 45 , 46 ]. These findings will need further investigation for validation.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Galleu et al found that triggering of T-cell mediated apoptosis may be a hallmark of MSC-immunomodulation in vivo [ 31 ]. Intriguingly, Bashoun et al found that highest apoptosis and lowest viability peaked at 4 and 24 h post-thawing, respectively, but that there was no difference between fresh and cryo MSCs in functional outcome [ 76 ]. Nonetheless, these studies demonstrate that increased T- and NK-cell recognition of thawed vs. fresh MSCs in the clinical setting should be anticipated (Fig.…”
Section: Mesenchymal Stromal/stem Cells (Mscs)mentioning
confidence: 99%
“…There is great clinical and commercial potential for employing cryopreserved MSC products with direct thawing and “bed-side” infusion of MSC products to patients [ 39 , 70 ], but there are still questions considering optimal manufacturing and standardization of this process. As Bahsoun et al pointed out [ 76 ], cryopreservation of MSCs may be considered an essential part of the process-chain for effective and economically viable distribution to healthcare facilities / patients, but differences in viability and functionality of cryo MSCs versus fresh MSCs cannot be overlooked.…”
Section: Mesenchymal Stromal/stem Cells (Mscs)mentioning
confidence: 99%